2013
DOI: 10.1007/s11250-013-0358-7
|View full text |Cite
|
Sign up to set email alerts
|

Live weight, carcass ultrasound images, and visual scores in Angus cattle under feeding regimes in Brazil

Abstract: This study aimed to evaluate visual precocity, muscling, conformation, skeletal, and breed scores; live weights at birth, at 205, and at 550 days of age; and, besides, rib eye area and fat thickness between the 12th and 13th ribs obtained by ultrasound. Those traits were evaluated in 1,645 Angus cattle kept in five feeding conditions as follows: supplemented or non-supplemented, grazing native pasture or grazing cultivated pasture, and feedlot. Descriptive statistics, Pearson's correlations, and principal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…The high correlation between longissimus muscle area and energy level after weaning is detected in Angus heifers (Hall et al, 1995). An important correlation between visual scores, live weights, and carcass traits obtained by ultrasound was found, which can be analyzed by univariate procedure (Pinto et al, 2013). Miar et al (2014) indicated that ultrasound measurements of backfat thickness and ribeye area have strong genetic correlations with the corresponding measurements of carcass merit.…”
Section: Discussionmentioning
confidence: 91%
“…The high correlation between longissimus muscle area and energy level after weaning is detected in Angus heifers (Hall et al, 1995). An important correlation between visual scores, live weights, and carcass traits obtained by ultrasound was found, which can be analyzed by univariate procedure (Pinto et al, 2013). Miar et al (2014) indicated that ultrasound measurements of backfat thickness and ribeye area have strong genetic correlations with the corresponding measurements of carcass merit.…”
Section: Discussionmentioning
confidence: 91%
“…Leite et al (2009) studied eleven quail carcass traits and the results were that only four traits were convenient in his study. Performance traits in Angus cattle are studied by (Pinto et al, 2013). It is found that four principal components of fifteen traits explained 80% of total variance.…”
Section: Introductionmentioning
confidence: 99%
“…É também um fator limitante do seu uso a deficiência do ensino da técnica e da interpretação dos resultados nas escolas veterinárias, o que impede a sua utilização de forma clinica por profissionais do ramo. Entretanto, a ultrassonografia tem sido comercialmente utilizada para avaliação da composição de carcaça em animais vivos e, principalmente, para avaliação reprodutiva de fêmeas domésticas (Pinto et al 2013, Hansar et al 2014. O exame dos órgãos internos como as vesículas seminais, ampolas dos ductos deferentes e próstata são estruturas que podem ser identificadas e avaliadas pela técnica de ultrassonografia (Koetz Junior 2015).…”
Section: Introductionunclassified